1995
DOI: 10.2527/1995.73113216x
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response effects of recombinant bovine somatotropin (PosilacTM) on growth performance and body composition of two-year-old rainbow trout (Oncorhynchus mykiss)

Abstract: Two hundred rainbow trout (Oncorhynchus mykiss, mean weight 301.5 g) were allotted to four treatments with five replicates in a randomized block design to determine the dose-response effects of recombinant bovine somatotropin (rbST; Posilac) on growth performance and carcass composition. Treatments were sham-injected controls (S), 10 micrograms/g BW of rbST (L), 20 micrograms/g BW of rbST (M), and 30 micrograms/g BW of rbST (H). The tanks held 135 L; water flow = 15.1 L/min; temperature = 15 degrees C. The fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…Previous experiments have shown that exogenous GH treatment and the production of GH transgenic fish result in a significant increase in overall growth rate in rainbow trout and other salmonids (21,39,52). In addition, studies have examined the effects of GH augmentation on aspects of physiology and gene expression in salmonids (3,4,26,44,57,66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have shown that exogenous GH treatment and the production of GH transgenic fish result in a significant increase in overall growth rate in rainbow trout and other salmonids (21,39,52). In addition, studies have examined the effects of GH augmentation on aspects of physiology and gene expression in salmonids (3,4,26,44,57,66).…”
Section: Discussionmentioning
confidence: 99%
“…In the rainbow trout, a 6-wk recombinant bovine somatotropin (rbST) treatment significantly increased weight and length (21). Determinations of the underlying biological pathways enhancing growth in the salmonids after recombinant bovine GH (rbGH) treatment have been limited to individual gene expression studies (3,4,5,26) and measurements of metabolic parameters (21,28,29,42,34,57).…”
mentioning
confidence: 99%
“…The increase in weight associated with growth in fish appears to be due to a combination of increased appetite [14, 15] and increased feed conversion [[14, 16, 17]; for review,see [18]]. In fish, both GH administration [19, 20] and GH transgenesis [21] result in increased growth that might be attributed to increased feeding and improved food assimilation [20, 22].…”
Section: Gh Regulation Of Growth and Metabolismmentioning
confidence: 99%
“…Growth of post larvae were measured carefully as total length were to nearest 0.1 mm and total weight to nearest 0.001 mg to calculate total weight gain, average daily gain, specific growth rate in weight were according to Castell [14], Condition factor were according to Yildiz et al [15] and average daily gain or increase in length were according to Garber [16] and specific growth rate in length were according to Nour [17].…”
Section: Growth Criteriasmentioning
confidence: 99%